Crime Of Selling Narcotics Class I (Analysis of Decision Number: 124/Pid.Sus/2022/PN Ksp) - Purwoko; Yasmirah Mandasari Saragih (International Journal of Society and Law, 2024)
Indonesia's strategic geographical location as an archipelagic country makes it a prime target for narcotics traffickers, serving both as a distribution point and a transit hub. The narcotics problem in Indonesia has worsened, now affecting not only teenagers from affluent backgrounds but also low-income and impoverished individuals. This widespread abuse spans all social strata and age groups. Profits from the lucrative drug trade drive traffickers to exploit various means, including new drugs, routes, technologies, and vulnerable individuals, such as children. An estimated 1.5% of Indonesia's population is involved in narcotics abuse, with minors being significantly affected. While narcotics have legitimate medical uses, public misconceptions and misuse have led to severe health impacts. Despite comprehensive monitoring and law enforcement efforts, including the Narcotics Law (Law Number 35 of 2009), narcotics crimes persist and even escalate. The law aims to enhance the role of the National Narcotics Agency (BNN) in tackling these crimes. However, recent cases, such as the prosecution of Fahrulsyah alias Keleng Bin Samsul Bahar for selling Class I narcotics, highlight ongoing challenges. This study, titled "Crime of Selling Class I Narcotics (Analysis of Decision Number: 124/Pid.Sus/2022/Pn Ksp)," examines the effectiveness of current legal frameworks in combating narcotics trafficking and abuse.